Fabrication and Optoelectrical Properties of IZO/Cu2O Heterostructure Solar Cells by Thermal Oxidation - Cheng-Chiang Chen; Lung-Chien Chen; Yi-Hsuan Lee (Advances in Condensed Matter Physics)
Indium zinc oxide (IZO)/cupper oxide (Cu2O) is a nontoxic nature and an attractive all-oxide candidate for low-cost photovoltaic (PV) applications. The present paper reports on the fabrication of IZO/Cu2O heterostructure solar cells which the Cu2O layers were prepared by oxidation of Cu thin films deposited on glass substrate. The measured parameters of cells were the short-circuit current (Isc), the open-circuit voltage (Voc), the maximum output power (Pm), the fill factor (FF), and the efficiency (η), which had values of 0.11 mA, 0.136 V, 5.05 μW, 0.338, and 0.56%, respectively, under AM 1.5 illumination.